2022
DOI: 10.1186/s13014-022-02171-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy modulates tumor cell fate decisions: a review

Abstract: Cancer has always been a worldwide problem, and the application of radiotherapy has greatly improved the survival rate of cancer patients. Radiotherapy can modulate multiple cell fate decisions to kill tumor cells and achieve its therapeutic effect. With the development of radiotherapy technology, how to increase the killing effect of tumor cells and reduce the side effects on normal cells has become a new problem. In this review, we summarize the mechanisms by which radiotherapy induces tumor cell apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 130 publications
0
17
0
1
Order By: Relevance
“…Therefore, to find out the downstream molecular markers involved in cell death, a DNA damage marker and a cell death marker were evaluated. H2AX phosphorylation (γH2AX) is a well-known marker of an early cellular response to DNA double-strand breaks, and Caspase 3 is a key molecule involved in cell death ( Chen et al, 2022 ; Widjaja et al, 2023 ). In this study, western blot analysis showed that Bi-212-MAA treatment induced H2AX phosphorylation in 4T1-treated cells ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to find out the downstream molecular markers involved in cell death, a DNA damage marker and a cell death marker were evaluated. H2AX phosphorylation (γH2AX) is a well-known marker of an early cellular response to DNA double-strand breaks, and Caspase 3 is a key molecule involved in cell death ( Chen et al, 2022 ; Widjaja et al, 2023 ). In this study, western blot analysis showed that Bi-212-MAA treatment induced H2AX phosphorylation in 4T1-treated cells ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, no change was seen in markers of radioresistance, specifically proteins involved in cell cycle checkpoint control. It is known that increased radiation dose can lead to cell cycle arrest and cell survival, making it critical to find a sensitive dose ( Chan Wah Hak et al, 2022 ; Chen et al, 2022 ; Widjaja et al, 2023 ). Alpha (α)-particle therapy works through direct double-stranded DNA breaks, thus leaving the cell with very few options for resistance and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our results preliminarily suggest that KCTD5 is involved in the regulation of tumor cell apoptosis, but the specific regulatory mechanism remains unclear. Regulation of the apoptosis signaling pathway is an important way to improve cancer therapy [ 27 , 28 ]. KCTD5 may be a potential target for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the most widely used conventional therapeutic strategies for cancer patients [ 1 ]. DNA double-strand breaks induced by ionizing radiation are one of the main mechanisms of its antitumor effect [ 2 ]. However, the serious side effects on the human body are a major concern in radiotherapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%